SAT0535 Carotid Ultrasound in The Cardiovascular Risk Stratification of Patients with Ankylosing Spondylitis: Results of A Population-Based Study. (15th July 2016) - Rueda-Gotor, J.; Fernández Díaz, C.; Llorca, J.; Corrales, A.; Blanco, R.; Fuentevilla, P.; Portillo, V.; Expόsito, R.; Mata, C.; Pina, T.; González-Juanatey, C.; Gonzalez-Gay, M.A.
Abstract : Objectives: To determine if the use of carotid ultrasonography (US) may improve the cardiovascular (CV) risk stratification in patients with ankylosing spondylitis (AS). Methods: A set of 127 consecutive patients without history of CV events, diabetes mellitus or chronic kidney disease that fulfilled definitions for AS according to the 1984 modified New York criteria were recruited to assess carotid intima-media thickness and presence of plaques. CV risk was calculated according to the systematic coronary risk evaluation (SCORE), the Framingham Risk Score (FRS) and the Reynolds Risk Score (RRS). Results: Men outnumbered women (61.4%). The mean±SD age at the time of the study was 44.5±11.6 years. The median (interquartile range) delay to the diagnosis was 5 (1–12) years. HLA-B-27 was positive in 77.2%, and syndesmophytes were present in 38.9%. Carotid plaques were found in 43 (33.9%). Regardless of the algorithm used for CV risk stratification, more than 50% of the patients classified as having moderate CV risk had carotid plaques. Moreover, 20.8%, 24.6% and 53.3% of AS that fulfilled the category of low CV risk according to the total cholesterol (TC)-SCORE, FRS and RRS, respectively had carotid plaques. A model that included patients with a chart TC-SCORE ≥5% or SCORE-TC ≥1% <5% plus carotid plaques or TC-SCORE <1% and CRP >3 mg/L at diagnosis plus syndesmophites and carotid plaques or TC-SCORE <1% and CRP >3 mg/L at diagnosis plus extraarticular manifestations plus carotid plaques yielded the highest sensitivity (93.0%) for high/very high CV risk in these patients. The presence of syndesmophytes was associated with increased risk of carotid plaques in AS that fulfilled definitions for low CV risk according to the TC-SCORE (OR 8.75 [95% CI 2.11 - 36.40]; p=0.002). Conclusions: Our results support the use of carotid US in the assessment of CV risk in patients with AS. Disclosure of Interest: None declared